1993
DOI: 10.1002/ange.19931050226
|View full text |Cite
|
Sign up to set email alerts
|

η6‐(1,2‐Dioxocyclobutabenzol)tricarbonylchrom(O): Edukt für doppelt anionische Oxy‐Cope‐Umlagerungen unter besonders milden Bedingungen

Abstract: Nature 1991,353, 642-644. Analytisch reine Proben erhllt man durch einfache Filtration, anschlie-Bendes Waschen mit wasserfreiem EtOH und MeCN und Trocknen im Vakuum bei 100°C fur 2-6 h. Korrekte C,H,Ba,Si-Analyse fur 1 '3.25 HOCH,CH,OH. Kristalldaten fur 1 . 3.25 HOCH,CH,OH: triklin P i , a =10.151(8), b = 13.865(5), c = 15.709(6) A, C( = 102.90(3), / l = 91.04(3), y = 109.75(3)", V = 2018(1)A3,Z= 4,eb,, =1.70gcm~',p(MoK.) = 2.08mm-',F(000) = 1080, farbloses rechteckiges Pllttchen, 0.2 x 0.5 x 0.44 mm3, 13038… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…After phase separation the organic layer was collected with a syringe and filtered into a Schlenk flask through a P4 frit covered with a 5 cm thick layer of MgSO 4 . After solvent removal 2,5-bis(trifluoromethylsulfonyl)ferrocenol (14) was isolated as an orange solid; yield: 2.00 g (17) 1-Methoxy-2,5-bis(trifluoromethylsulfonyl)ferrocene (15) At À78 8C LDA in THF [prepared from 1.6 M n-BuLi (2.7 mL, 4.4 mmol) in hexane and diisopropylamine (1.9 mL, 13.2 mmol) in THF (20 mL)] was added dropwise over 40 min to 2-(trifluoromethylsulfonyl)ferrocenyl triflate (13, 1.8 g, 4.4 mmol) in THF (20 mL). The color changed from light yellow to deep red.…”
Section: 5-bis(trifluoromethylsulfonyl)ferrocenol (14)mentioning
confidence: 99%
See 1 more Smart Citation
“…After phase separation the organic layer was collected with a syringe and filtered into a Schlenk flask through a P4 frit covered with a 5 cm thick layer of MgSO 4 . After solvent removal 2,5-bis(trifluoromethylsulfonyl)ferrocenol (14) was isolated as an orange solid; yield: 2.00 g (17) 1-Methoxy-2,5-bis(trifluoromethylsulfonyl)ferrocene (15) At À78 8C LDA in THF [prepared from 1.6 M n-BuLi (2.7 mL, 4.4 mmol) in hexane and diisopropylamine (1.9 mL, 13.2 mmol) in THF (20 mL)] was added dropwise over 40 min to 2-(trifluoromethylsulfonyl)ferrocenyl triflate (13, 1.8 g, 4.4 mmol) in THF (20 mL). The color changed from light yellow to deep red.…”
Section: 5-bis(trifluoromethylsulfonyl)ferrocenol (14)mentioning
confidence: 99%
“…[13] In contrast, there is strong mass spectrometric evidence for the (benzyne)Cr + cation with the chromium atom attached at the cyclic p system. [14] As a matter of fact, the respective MS peak at m/z = 128 is the base peak in mass spectra of tricarbonylchromium complexes of benzocyclobutenedione, [14,15] indantrione, [16] indan-1,3-dione, [16] and acetals thereof as a result of fragmentation reactions. These findings caused our interest in the synthesis or trapping of p complexes of arynes and related systems.…”
Section: Introductionmentioning
confidence: 98%
“…The reaction sequence proved to be highly diastereoselective and makes highly substituted polycyclic systems available in a very efficient way. [22,23,[33][34][35][36][37][61][62][63] It was also shown that the vinyllithium diaddition followed by a dianionic oxy-Cope rearrangement works with uncoordi- nated indan-1,2-dione, albeit in only moderate yield. [64] We envisaged the possibility that the electron withdrawal from the tricarbonylchromium group in 5 might help to improve the allkenyllithium diaddition yield and thereby allow the rearrangement to take place with better overall yield.…”
Section: % De (Gc)mentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] We have contributed to this development in our investigations in the field of (arene)tricarbonylchromium complexes with functionalized anellated rings. [22][23][24] Key compounds in our research are complexes 1-4 of benzocyclobutenone, [22,[25][26][27][28][29][30][31] benzocyclobutenedione, [27,29,30,[32][33][34][35][36][37] 1,3-indandione, [38] and 1,2,3-indantrione. [38] In particular, chemistry relating to 1 and 2 has unveiled important oxy anion-accelerated reactions, such as anionic ring-opening reactions or dianionic oxyCope rearrangements, which take place under particularly mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…When 2 equiv. of vinyllithium are added to (benzocycloThe twofold addition of organometallics to squarate esters had not been extensively examined at the time that our butenedione)tricarbonylchromium, the double addition occurs in cis fashion because of steric constraints [26] . Distudies were initiated.…”
mentioning
confidence: 99%